The Effect of Work Environment, Work Motivation, and Compensation on Employee Performance: JEL Classification: J24, J33, M12, M54 - Kristianto, Fajar; Nisa, Aribia Razzina Ainun; Junaedi, Seftyan Pamungkas; Narensa, Verena Pruedira (Journal La Bisecoman, 2025)
This study aims to examine the influence of work environment, work motivation, and compensation on employee performance through a literature review approach. The study uses a literature review method by analyzing journals published in the last ten years. The population consists of previous relevant studies, with samples from national and international journals discussing the related variables. The research design is descriptive with content analysis techniques to identify patterns of relationships among variables. The results show that work environment, work motivation, and compensation generally have a positive and significant effect on employee performance, both partially and simultaneously. The novelty lies in the systematic mapping of findings from various studies to provide a comprehensive picture of the relationships among these variables. Companies are advised to improve the quality of the physical and non-physical work environment, enhance fair compensation systems, and manage motivation factors effectively.